Analisis Perhitungan Persediaan Barang Dagang Dengan Metode Average Pada Usaha Telur Asin Oma Liez - Khairunnisa, Fadhila; Rahmi, Fadia; Agustina, Lia; Setiawan, M Rizky Thessar; Handayani, Monika (P3M Politeknik Negeri Banjarmasin, 2023)
This study aims to determine the management of trade goods inventory in the Oma Liez Salted Egg Business in the period October to December 2022. The method applied in this study is the Average method which was developed from purchase and sales data of trade goods inventory. The results showed that the Average method applied to inventory valuation can help reduce the problems that occur in the Salted Egg Business related to the inventory of trade goods, because it is considered very effective by producing a low cost of goods sold and a greater opportunity to increase profits. This method is better than the method used previously in inventory valuation which resulted in problems that affected revenue.